RADON AND CARCINOGENIC RISK IN MOSCOW - S. M. Golovanev (Радиационная гигиена)
Objective: comparative evaluation of carcinogenic risk inMoscowfrom radon in indoor and atmospheric pollutants.Materials and methods: the lung cancer incidence in Moscow; radiation-hygienic passport of the territory; .U.S. EPA estimated average age at all and radon induced deaths, years of life lost; Report of UNSCEAR 2006 and WHO handbook on indoor radon, 2009. Trend analysis of incidence; evaluation of the excess relative risk; assessment of ratio radon-induced population risk and published values оf total population carcinogenic risk from chemical carcinogens.Results: it is shown that the 304 cases of lung cancer per year (1. 85 10-3) on average from 2006 to 2011 (21280diseases for 70 years in addition to background level) induced by radon; the differences in average trends of all lungcancer incidence in the districts can exceed 25%.Conclusion. The potential of risk reduction by measures of mitigation radon concentration exceeds 5 times the cost efficiency to reduce emissions from vehicles and can reduce cancer incidence, on average 236 cases per year; population risk 16520 cases over 70 years or save not less than 2832 person-years of life per year. The annual effect of reducing losses from not-survival of 12 years as a result of radon-induced lung cancer deaths exceeds 14160000 dollars. The evaluating of the carcinogenic risk from radon in accordance with the definition of population risk increases the predictive evaluation of the effectiveness of preventive measures more than twice.